2016
DOI: 10.4172/2155-9864.1000366
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in Pregnant Women of Sokoto Residents in North Western Nigeria

Abstract: Background: In developing countries, anaemia is a cause of serious concern as it contributes significantly to high maternal mortality. The aim of this study was to assess the prevalence of anaemia among pregnant women in Sokoto, Northern Nigeria due to scanty information in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Hematocrit level was used to determine the anaemic status of the study participants. It was determined by using a micro hematocrit centrifuge as described elsewhere [21].The hematocrit level was read by using a Hawksley microhematocrit reader. According to WHO guidelines, pregnant women are average, with hematocrit value of 33% and above.…”
Section: Anaemia Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematocrit level was used to determine the anaemic status of the study participants. It was determined by using a micro hematocrit centrifuge as described elsewhere [21].The hematocrit level was read by using a Hawksley microhematocrit reader. According to WHO guidelines, pregnant women are average, with hematocrit value of 33% and above.…”
Section: Anaemia Determinationmentioning
confidence: 99%
“…The pregnant women with hematocrit values less than 33% were categorized as anemic. Anemia was further classified as mild ( ≥ 30 to < 33%) or moderate ( ≥ 21 to < 30%) or severe ( < 21.0%) [21].…”
Section: Anaemia Determinationmentioning
confidence: 99%
“…Meanwhile, recent reports such as Olatunbosun et al (2014), Buhari et al (2016) and Omote et al (2020) showed anaemia prevalence values of 55%, 86% and 38% among pregnant women in Uyo, Sokoto and Warri areas of Nigeria respectively.…”
Section: Introductionmentioning
confidence: 97%
“…Such factors are maternal age at index pregnancy, gestational age of index pregnancy, parity, booking status and birth interval [11,30,31]. It is a well-documented fact that extremes of age (adolescent and women above 40 years) have been associated with anaemia in pregnancy with many of these studies showing that anaemia is more common in adolescence than adult women [11,30,32,33]. Apart from the maternal age the association between gestational age of pregnancy and anaemia has been widely studied [11,30,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…It is a well-documented fact that extremes of age (adolescent and women above 40 years) have been associated with anaemia in pregnancy with many of these studies showing that anaemia is more common in adolescence than adult women [11,30,32,33]. Apart from the maternal age the association between gestational age of pregnancy and anaemia has been widely studied [11,30,[32][33][34][35]. In normal pregnancy, there is an increase in the total blood volume different from that in the non-pregnant state.…”
Section: Introductionmentioning
confidence: 99%